2021
DOI: 10.3390/w13070937
|View full text |Cite
|
Sign up to set email alerts
|

How Flood Hazard Maps Improve the Understanding of Ecologically Active Floodplains

Abstract: Floodplains are threatened ecosystems and are not only ecologically meaningful but also important for humans by creating multiple benefits. Many underlying functions, like nutrient retention, carbon sequestration or water regulation, strongly depend on regular inundation. So far, these are approached on the basis of what are called ‘active floodplains’. Active floodplains, defined as statistically inundated once every 100 years, represent less than 10% of a floodplain’s original size. Still, should this remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Günther-Diringer et al [27] identified 43% of the active floodplains as grassland while 26% is arable land. Forests are of minor importance and range, depending on the methodology applied, between less than 10% [40] and 16% [35]. Settlements, transport infrastructure, and commercial facilities make up about 7%.…”
Section: Floodplain Land Use and Habitat Typesmentioning
confidence: 99%
“…Günther-Diringer et al [27] identified 43% of the active floodplains as grassland while 26% is arable land. Forests are of minor importance and range, depending on the methodology applied, between less than 10% [40] and 16% [35]. Settlements, transport infrastructure, and commercial facilities make up about 7%.…”
Section: Floodplain Land Use and Habitat Typesmentioning
confidence: 99%